Effect of interactive cognitive motor training on gait and balance among older adults: A randomized controlled trial - Kao, Ching-Chiu; Chiu, Huei-Ling; Liu, Doresses; Chan, Pi-Tuan; Tseng, Ing-Jy; Chen, Ruey; Niu, Shu-Fen; Chou, Kuei-Ru (International journal of nursing studies, 2018)
Aging is a normal degenerative process that results in a decline in the gait and balance performance of older adults. Interactive cognitive motor training is an intervention that integrates cognitive and motor tasks to promote individuals’ physical and cognitive fall risk factors. However, the additive effects of the interactive cognitive motor training on objective quantitative data and comprehensive descriptions of gait and balance warrants further investigation. To investigate the effect of interactive cognitive motor training on older adults’ gait and balance from immediate to long-term time points. A double-blind randomized control trial. Four senior service centers and community service centers in Taiwan. 62 older adults who met the inclusion criteria. The study participants were older adults without cognitive impairment, and they were randomly allocated to the experimental group or active control group. In both groups, older adults participated in three sessions of 30-min training per week for a total of 8 weeks, with the total number of training sessions being 24. The primary outcome was gait performance, which was measured using objective and subjective indicators. iWALK was used as an objective indicator to measure pace and dynamic stability; the Functional Gait Assessment was employed as a subjective indicator. The secondary outcome was balance performance, which was measured using iSWAY. A generalized estimating equation was used to identify whether the results of the two groups differ after receiving different intervention measures; the results were obtained from immediate to long-term posttests. Stride length in the pace category of the experimental group improved significantly in immediate posttest (p = 0.01), 3-month follow-up (p = 0.01), and 6-month follow-up (p = 0.04). The range of motion of the leg exhibited significant improvement in immediate posttest (p = 0.04) and 3-month follow-up (p = 0.04). The Functional Gait Assessment result indicated that statistically significant improvement was observed in immediate posttest (p = 0.02) and 12-month follow-up (p = 0.01). The results of balance performance showed that the experimental group attained statistically significant improvement in centroid frequency in the immediate posttest (p = 0.02). The research results validated that the 24 sessions of the interactive cognitive motor training intervention significantly improved gait and balance performance. Future studies should extend the sample to communities to promote the gait and balance performance of community-dwelling older adults without cognitive impairment and reduce their risk of falling and developing gait-related diseases.